Orientations Mapping Studies in the Asian Diaspora - Chuh, Kandice; David, Liu; Dipesh, Chakrabarty; Dorinne, Kondo; George, Lipsitz; Kandice, Chuh; Karen, Shimakawa; Kuan, Chen; Lisa, Lowe; Martin, Manalansan; R, Radhakrishnan; Rey, Chow; et al. (Duke University Press, 2001)
Asian and Asian American studies emerged, respectively, from Cold War and social protest ideologies. Yet, in the context of contemporary globalization, can these ideological distinctions remain in place? Suggesting new directions for studies of the Asian diaspora, the prominent scholars who contribute to this volume raise important questions about the genealogies of these fields, their mutual imbrication, and their relationship to other disciplinary formations, including American and ethnic studies.With its recurrent themes of transnationalism, globalization, and postcoloniality, Orientations considers various embodiments of the Asian diaspora, including a rumination on minority discourses and performance studies, and a historical look at the journal Amerasia. Exploring the translation of knowledge from one community to another, other contributions consider such issues as Filipino immigrants' strategies for enacting Asian American subjectivity and the link between area studies and the journal Subaltern Studies. In a section that focuses on how disciplines-or borders-form, one essay discusses "orientalist melancholy," while another focuses on the construction of the Asian American persona during the Cold War. Other topics in the volume include the role Asian immigrants play in U.S. racial politics, Japanese American identity in postwar Japan, Asian American theater, and the effects of Asian and Asian American studies on constructions of American identity.Contributors. Dipesh Chakrabarty, Kuan-Hsing Chen, Rey Chow, Kandice Chuh, Sharon Hom, Yoshikuni Igarashi, Dorinne Kondo, Russell Leong, George Lipsitz, Lisa Lowe, Martin F. Manalansan IV, David Palumbo-Liu, R. Radhakrishnan, Karen Shimakawa, Sau-ling C. Wong